Nghiên cứu đánh giá độ phong phú, tương đồng của loài ve sầu (Hemiptera: Cicadidae) ở khu vực Tây Bắc. - Hoang, Yen Luu (2025)
There have been many research works on cicadas of the Cicadidae, but they have only researched and evaluated diversity in a conservation area, or a national park in the Northwest, without a comprehensive study on them. In this study, the authors have collected and used biodiversity indices to calculate biodiversity indexes of cicadas in the Northwest region. Results showed that the cicada species in the Cicadidae had the highest diversity in the old-growth forest ecosystem, decreasing gradually in the secondary forest ecosystem and the lowest in the secondary forest ecosystem...